Bioinspired surfaces with superwettability for anti-icing and ice-phobic application : concept, mechanism, and design - Zhang, Songnan (2019)
Ice accumulation poses a series of severe issues in daily life. Inspired by the nature, superwettability surfaces have attracted great interests from fundamental research to anti‐icing and ice‐phobic applications. Here, recently published literature about the mechanism of ice prevention is reviewed, with a focus on the anti‐icing and ice‐phobic mechanisms, encompassing the behavior of condensate microdrops on the surface, wetting, ice nucleation, and freezing. Then, a detailed account of the innovative fabrication and fundamental research of anti‐icing materials with special wettability is summarized with a focus on recent progresses including low‐surface energy coatings and liquid‐infused layered coatings. Finally, special attention is paid to a discussion about advantages and disadvantages of the technologies, as well as factors that affect the anti‐icing and ice‐phobic efficiency. Outlooks and the challenges for future development of the anti‐icing and ice‐phobic technology are presented and discussed.